Anesthetic Technique and the Cytokine and Matrix Metalloproteinase Response to Primary Breast Cancer Surgery. Issue 6 (1st October 2010) - Deegan, Catherine A.; Murray, David; Doran, Peter; Moriarty, Denis C.; Sessler, Daniel I.; Mascha, Ed; Kavanagh, Brian P.; Buggy, Donal J.
Abstract : Background: Breast cancer is the most common malignancy in women. Surgery remains the most effective treatment. Several perioperative factors, including the surgical stress response, many anesthetics and opioids, adversely affect immune function. Regional anesthesia-analgesia attenuates perioperative immunosuppression. We tested the hypothesis that patients who receive combined propofol/paravertebral anesthesia-analgesia (propofol/paravertebral) exhibited reduced levels of protumorigenic cytokines and matrix metalloproteinases (MMPs) and elevated levels of antitumorigenic cytokines compared with patients receiving sevoflurane anesthesia with opioid analgesia (sevoflurane/opioid). Methods: Primary breast cancer surgery patients were randomized to propofol/paravertebral (n = 15) or sevoflurane/opioid (n = 17) and preoperative and postoperative serum concentrations of 11 cytokines (interleukin 1β [IL-1β], IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p70, IL-13, interferon γ, and tumor necrosis factor α) and 3 MMPs (MMP-1, MMP-3, and MMP-9) were measured. Results: Treatment groups were well balanced for age, weight, surgical procedure, and cancer pathologic diagnosis. Pain scores were lower at 1 and 2 hrs with paravertebral analgesia compared with morphine but similar at 24 hrs. Patients in the propofol/paravertebral group showed a greater percentage decrease in postoperative compared with preoperative IL-1β (median [quartiles], −26% [−15% to −52%] versus −4% [−14% to 2%], P = 0.003), a significant attenuation in elevated MMP-3 (2% [−39% to 12%] versus 29% [23%-59%], P = 0.011) and MMP-9 (26% [13%-54%] versus 74% [50%-108%], P = 0.02), and a significant increase in IL-10 (10% [5%-33%] versus −15% [20% to −2%], P = 0.001) compared with sevoflurane/opioid group. No significantly different changes in IL-2, IL-4, IL-5, IL-6, IL-8, IL-12p70, IL-13, interferon γ, tumor necrosis factor α, or MMP-1 were observed between the 2 groups. Conclusions: Propofol/paravertebral anesthesia-analgesia for breast cancer surgery alters a minority of cytokines influential in regulating perioperative cancer immunity. Further evaluation is required to determine the significance of these observations.